Behaviour change in post-consumer recycling: Applying agent-based modelling in social experiment. (20th June 2018) - Tong, Xin; Nikolic, Igor; Dijkhuizen, Bob; van den Hoven, Maurits; Minderhoud, Melle; Wäckerlin, Niels; Wang, Tao; Tao, Dongyan
Abstract: Change in consumer behavior that leads to increased waste separation and recycling has been identified as a critical component of Chinese national strategy for constructing a "Circular Economy". Various innovative solutions at community level targeting consumer behaviors are emerging in Chinese cities, using information technology that can track the volume and quality of the sorting process. In order to evaluate the potential impact of these novel solutions, we studied the behavioral change of households by initiating an experimental recycling program in a residential community in Beijing, and developed an Agent Based Model based on Theory of Planned Behavior (TPB) to identify key factors in changing behavior. The results show that the Social Norm (SN) has a decisive effect on whether an area starts recycling or not. As to the effectiveness of intervention, the Perceived Behavioral Control (PBC) plays a large role in the determination of the recycling behavior in this study, while the role of attitude is relatively small. The model outcomes can be corroborated with observations in different communities using similar technical solutions. In conclusion, we suggest that efficient local interactions among various stakeholders are needed in forming the social norm and common space that favorite recycling activities at the community level.